2017
DOI: 10.14744/nci.2017.57984
|View full text |Cite
|
Sign up to set email alerts
|

Single-sided synonasal mass, retrospective study

Abstract: OBJECTIVE:A unilateral sinonasal mass is a common pathology in ear, nose, and throat clinical practice. However, it may be confused with early stage inflammatory pathologies. The aim of this study was to examine the diagnostic histopathological, clinical, and radiological criteria for a unilateral nasal mass.METHODS:The present study examined the clinical and pathological profiles of unilateral sinonasal masses observed in patients at an ear, nose, and throat clinic in Istanbul between January 2008 and January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
4
7
0
3
Order By: Relevance
“…8,9 Some studies even reported a higher prevalence of benign histopathological diagnosis of UNM's of 95.9%. 15 Our study showed 76.0% benign, and the remaining 24.0% were malignant.…”
Section: Resultsmentioning
confidence: 47%
“…8,9 Some studies even reported a higher prevalence of benign histopathological diagnosis of UNM's of 95.9%. 15 Our study showed 76.0% benign, and the remaining 24.0% were malignant.…”
Section: Resultsmentioning
confidence: 47%
“…Unilateral nasal discharge, nasal congestion and nose bleeding in addition to dysosmia, migraine, and facial swelling are most common presenting clinical complaints in patients with unilateral nasal disease (7)(8)(9). Clinical characterization of a patient complaining of single-sided nasal symptoms mass is an essential challenging health issue because they are often accompanied by multifactorial underlying etiology (1,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical characterization of a patient complaining of single-sided nasal symptoms mass is an essential challenging health issue because they are often accompanied by multifactorial underlying etiology (1,8,9). Evaluation of such health issue should include good history taking, thorough local examination and endoscopic investigation in addition to radiologic evaluation (1,7). Findings on imaging play a significant role in the diagnosis and workup of sinonasal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Tek taraflı sinonazal hastalıklara sık rastlanmasına rağmen literatürde bu hastalık grubunu analiz eden çalışma sayısı oldukça azdır (5). Bu retrospektif çalışmada kliniğimize tek taraflı sinonazal semptomlarla başvuran ve ameliyat edilip kesin tanısı konan hastalar semptom ve histopatolojik tanıları yönünden analiz edilmiştir.…”
Section: Introductionunclassified